Psicologia Escolar na Educação de surdos: desafios e possibilidades - Marega, Ana Carolina Marques (2024)
The objective of this research is to understand the possibilities of contribution of School Psychology in the Education of the deaf, considering the demands generated by the inclusion policy and the knowledge of psychologists regarding their professional practice in the area. This research was carried out in the Postgraduate Program in Psychology at the Federal University of Goiás, in the research line: Psychosocial and Educational Processes. The study is based on Vygotsky's historical-cultural perspective and, in order to achieve the proposed objective, a combination of procedures was developed, namely: literature review, document analysis and application of questionnaires to the psychologists. A quantitative-descriptive and qualitative analysis of the literature review was carried out, which led to the conclusion that most of the selected texts address issues related to the Education of the deaf, with some being based on concepts from Psychology to discuss the development and learning process with this audience, and few texts specifically addressing the relationship between School Psychology and Education of the deaf. A documentary analysis of legislation in force in Brazil regarding inclusive education and deaf education was carried out. Finally, in the analysis of the questionnaires applied to thirty psychologists, two categories were organized: Characterization of the participants and experience with deaf education; and Knowledge of psychologists about school psychology and deaf education. In general, the results of the questionnaires indicated, based on the participants' knowledge, the need for structural support in schools and continued training for professionals to work with deaf students; the understanding that educational policies represent a challenge, but also a step forward in guaranteeing students' rights. Many challenges were observed for the work of school psychologists in deaf education, but possibilities were also identified, covering educational policies and the development of research